Korean traditional landscape architecture - Sim, U-gyŏng 1949- (Hollym, 2007)
Korean traditional landscape architecture is among the most treasured cultural developments made over the thousands of years of Korean culture. "Korean Traditional Landscape Architecture" illustrates the history and cultural background of Korean traditional landscape architecture, showing the characteristics of each type of Korean landscape architecture - royal palaces, residential areas, walled towns, retreat gardens, pavilions, Buddhist temples, private academies, and village groves. Thirteen writers collaborated to guide readers on a journey through Korean traditional landscape architecture to highlight the excellence of this Korean cultural heritage as well as the traditional Korean aesthetic and worldview.